2013
DOI: 10.1016/j.apsusc.2012.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Structure, reactivity, electronic configuration and magnetism of samarium atomic layers deposited on Si(001) by molecular beam epitaxy

Abstract: The surface structure, interface reactivity, electron configuration and magnetic properties of Sm layers deposited on Si(001) at various temperatures are investigated by low-energy electron diffraction (LEED), X-ray photoelectron spectroscopy (XPS), X-ray absorption spectroscopy (XAS) and magneto-optical Kerr effect (MOKE). It is found that metal Sm is present on samples prepared at low temperature, with an interface layer containing SmSi 2 and Sm 4 Si 3. When samples are prepared at high temperature, much les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Previous quantitative analyses when using these factors have given reasonable results, applied to our setup [45,48,49,61]. Only for rare earths had these ASF to be slightly adjusted [22,23]. It may also be observed that the results obtained by using Ge 2p and Ge 3d do not deviate that much.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Previous quantitative analyses when using these factors have given reasonable results, applied to our setup [45,48,49,61]. Only for rare earths had these ASF to be slightly adjusted [22,23]. It may also be observed that the results obtained by using Ge 2p and Ge 3d do not deviate that much.…”
Section: Resultssupporting
confidence: 62%
“…This is one of the few reports to our knowledge where a quite thick metal film is deposited onto a semiconductor and preserves its crystal structure and even its surface reconstruction. In the case of high temperature deposition of Fe on Si(001) (2 × 1)−(1 × 2) by using exactly the same setup, the LEED pattern vanishes starting with 1 nm of Fe thickness [ 20 , 21 ]; in the case of Sm/Si(001), a broad LEED pattern subsisted up to about 3.5 nm of Sm deposited [ 22 , 23 ]. A case closer to the present one was presented by Fe deposited in Ge(001) by keeping the substrate at high temperature (500 °C) [ 24 ], where the (1 × 1) LEED pattern of Ge(001) subsisted after 2 nm of Fe deposited; however, without providing also the (2 × 1)−(1 × 2) surface reconstruction of Ge(001).…”
Section: Resultsmentioning
confidence: 99%
“…As argued in ref. 62, each line from the simulations has its own associated inelastic background, expressed as an integral of the Voigt line; a vanishing value for this inelastic background coefficient indicates that the origin of these components is surface atoms.…”
Section: Characterizationmentioning
confidence: 99%
“…It may be surprising to attribute a higher binding energy component to Ge reacted with Fe, since usually semiconductors reacting with metals develop lower binding energy components [26,27]; however, for Fe–Ge, a similar binding energy (29.8 eV) was reported in [22]. The Fe(1):Ge(2) ratios represented in the next to the last column in Table 1 suggests the presence of surface compounds of approximate compositions ranging from FeGe 3 to Fe 3 Ge 5 , as indicated in the last column of Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, few LEED patterns are obtained for metals deposited on semiconductors. In [ 10 ], Fe/Si(001) exhibited a LEED pattern only up to about 0.8 nm of Fe deposited, whereas in [ 26 , 27 ] Sm/Si(001) deposited at 300 °C showed a very diffuse LEED pattern for 3.2 nm of Sm deposited. Here, we obtained clear LEED patterns for the equivalent of 1.7 nm Fe deposited.…”
Section: Resultsmentioning
confidence: 99%